2020
DOI: 10.1097/scs.0000000000006149
|View full text |Cite
|
Sign up to set email alerts
|

Catgut and its Use in Plastic Surgery

Abstract: The aim of this paper is to review the origin, physical properties, advantages, and usage of catgut in plastic surgery and oral surgery. In PubMed search, the search terms (“catgut” AND [“plastic surgery” OR “facelift”]) and (“catgut” AND “oral surgery”) were used, resulting in 28 and 30 papers, respectively. Of those 58 papers, 31 papers were excluded. Eight other papers were added; therefore, 35 papers were analyzed. Catgut has been used in cleft palate surgery since 1938. In 1976, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Additionally, their meat is a rich source of protein and can aid in reducing the protein malnutrition gap among consumers ( Nair et al, 2021 ). The goat intestine is used to make the catgut, which is still used as a material for internal human surgical sutures and strings for musical instruments ( Kim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, their meat is a rich source of protein and can aid in reducing the protein malnutrition gap among consumers ( Nair et al, 2021 ). The goat intestine is used to make the catgut, which is still used as a material for internal human surgical sutures and strings for musical instruments ( Kim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that none of the suture materials hindered wound healing, and there was a low incidence of wound complications with all of the used suture materials that did not reach statistical significance [ 19 ]. Other reports advocate the use of catgut as an absorbable suture as it is absorbable, has good tensile strength, is more comfortable for the patients as it spares them the pain of suture removal, leads to excellent wound healing, and has comparable rates of complications to other absorbable and non-absorbable suture materials [ 14 , 15 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Catgut's capacity for withstanding tension and its ability to last make it the perfect material for sutures [12].…”
Section: Catgutmentioning
confidence: 99%
“…Ongoing research aims to further explore the properties of catgut and develop new methods for their use, potentially finding applications in other medical fields. While catgut has limitations, its unique properties and potential benefits make it an area of focus for research and development in the medical field [12].…”
Section: Biodegradable Implanted Systemsmentioning
confidence: 99%